Camp Aruga : Leadership Growth, Compassion Outcomes, and Chapter Engagement Among Filipino American Nurses - Fe Rosario Antequino; Janette V. Moreno; Mary Dioise Ramos; Marlon Garzo Saria; Manny Ramos; Gloria Lamela Beriones; Lorraine S. Evangelista (Journal of Transcultural Nursing, 2026)
Introduction: Camp Aruga is a culturally grounded leadership bootcamp, integrating Filipino values, reflective dialogue, and Watson Caring Science ® to foster leadership, resilience, and self-care among Filipino American nurses. This evaluation examined pre- to post-program changes in leadership goals and Caring Science outcomes in Fall 2025. Methods: A pre–post design with surveys before and within 48 hr after the 2-day bootcamp. Of 48 attendees, 41 completed the pre-survey, 33 the post-survey, 26 matched leadership responses, and 25 Watson Caritas Self-Rating Score ® items. Outcomes included four leadership items (unity, governance, engagement/resilience, health equity advocacy) and five Watson Caritas items. Results: Among matched leaders, high achievement rose for all four goals; Caritas scores increased for all five items, with gains in loving-kindness toward self and self-care and in helping–trusting relationships, caring environments, and spirituality. Discussion: A Caring Science–informed framework may boost leadership confidence and self-care; longer-term studies are warranted to assess sustained effects.